Analysis Of Property Financing Development Using Musyarakah Mutanaqisah Contract At Islamic Banks In Medan City With ANP BOCR Approach - Rahma, Putri; M. Nawawi, Zuhrinal; Nurbaiti, Nurbaiti (Dinasti Publisher, 2024)
This study aims to analyze the problem of developing mutanaqisah musyarakah contracts in property financing by reviewing the benefits, opportunities, costs, and risks involved in mutanaqisah musyarakah contracts. This research uses a mix method between qualitative and quantitative with the ANP BOCR approach with the help of superdecision software. This research consists of four stages of research including pre-research, data collection, data processing and interpretation of results. The results of this study indicate that the ANP BOCR analysis regarding the development of property financing using the musyarakah mutanaqisah contract which is the top priority in the BOCR criteria aspect is Benefit with a Normalize value of 0.35644, followed by the risk aspect in second place with a value of 0.32573, followed by the opportunity aspect with a value of 0.19358 and in the last rank is the cost aspect with a value of 0.12426. The top priority in alternative strategies in developing property financing using the musyarakah mutanaqisah contract is the strategy that banks must work with honest developers. The next strategy is a socialization strategy, namely the bank conducts socialization to the public so that people understand more about the mutanaqisah musyarakah contract. In the third rank is to develop competitive and innovative products. Furthermore, the last rank is a promotion strategy in the form of banners, banners and billboards. Based on the calculation of the benefit cluster, each cluster has the same value, it means that the three benefit subcriteria have the same priority. Furthermore, in the opportunity cluster, the top priority is the development of property investment, followed by product innovation and needs according to the financing contract. Then in the cost cluster, the priority of the cost cluster is notary fees, followed by insurance costs in second place and administrative costs in third place. And in the risk cluster, the priority is credit risk, followed by market risk and compliance risk.